PENGARUH KUALITAS PRODUK, DAN PROMOSI TERHADAP MINAT BELI PENGGUNA E-COMMERCE BLIBLI DI BATAM - Sidabutar, Tom Berry Eduart; Saputra, S.E., M.Si., Asron (SCIENTIA JOURNAL, 2023)
Research that aims to find the results of the hypothesis on each variable studied.The hypothesis studied was to determine the effect of product quality andpromotion on buying interest of Blibli e-commercial users in Batam. The researchexamined 398 residents of the Beduk tj.Piayu sei. then the research will producecalculations using SPSS version 26. In the research the effect test on productquality t test (X1) is obtained 16.636 > t table 1.971 and 0.000 significant < 0.05.This means that product quality has a positive and significant effect on PurchaseIntention. So the first hypothesis can be accepted. The t test on Promotion (X2)obtained 20.636 > t table 1.971 and was significant 0.000 <0.05. This means thatpromotion has a positive and significant effect on buying interest. Then the secondhypothesis can be accepted